6 - Opposition Politics and Electoral Democracy in Cameroon, 1992-2007 - Ngwane, George (Africa Development, 2021)
This article seeks to assess the impact of electoral democracy in Cameroon especially in terms of the performance of the Opposition between 1992 and 2007, evaluate the internal shortcomings of opposition parties, and make a projection regarding a vibrant democratic space that will go beyond routine elections to speak to the issues preoccupying the Cameroonian masses.